The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fpubh.2022.1069219
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effects of health behavior and sports participation on female college students' body mass index and healthy promoting lifestyle

Abstract: ObjectiveLife form and body composition may affect the health of college students. This study will explore the relationship between the demographic variables of female college students and their body composition and health promoting lifestyle, so as to provide useful reference for the future design and planning of college students' physical and mental health courses and improving their physical activity level.MethodsUsing the method of questionnaire and bioelectrical resistance measurement, a questionnaire on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…As is known, our sensations, thoughts, feelings, emotions, mood and internal attitudes allow us to «press the reset button» of the human mind(Ghosh et al, 2021) and directly affect the psychophysiological processes, somatic health and life expectancy.For this reason, in accordance with the latter research aim, and taking into account the identified decline in psychosomatic health in young participants, we applied to them in practice several simple effective means to improve subjective wellbeing and reduce anxiety, stress. We guess that the aforementioned ancient Eastern techniques can serve as an effective, low-cost and easily applicable means of normalizing the psychophysiological functions, which are as beneficial as sports(Lin, & Liu, 2023;Stoduto et al, 2023;Yuan et al, 2022),…”
mentioning
confidence: 99%
“…As is known, our sensations, thoughts, feelings, emotions, mood and internal attitudes allow us to «press the reset button» of the human mind(Ghosh et al, 2021) and directly affect the psychophysiological processes, somatic health and life expectancy.For this reason, in accordance with the latter research aim, and taking into account the identified decline in psychosomatic health in young participants, we applied to them in practice several simple effective means to improve subjective wellbeing and reduce anxiety, stress. We guess that the aforementioned ancient Eastern techniques can serve as an effective, low-cost and easily applicable means of normalizing the psychophysiological functions, which are as beneficial as sports(Lin, & Liu, 2023;Stoduto et al, 2023;Yuan et al, 2022),…”
mentioning
confidence: 99%